2010
DOI: 10.1016/j.cub.2010.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Crumbs Regulates Salvador/Warts/Hippo Signaling in Drosophila via the FERM-Domain Protein Expanded

Abstract: Summary Background Altered expression of apicobasal polarity factors is associated with cancer in vertebrates and tissue overgrowth in invertebrates, yet mechanisms by which these factors affect growth regulatory pathways are not well defined. We have tested the basis of an overgrowth phenotype driven by the Drosophila protein Crumbs (Crb), which nucleates an apical membrane complex that functionally interacts with the Par6/Par3/aPKC and Scrib/Dlg/Lgl apicobasal polarity complexes. Results We find that Crb-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
333
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(357 citation statements)
references
References 52 publications
17
333
2
Order By: Relevance
“…Overexpression of full-length Crb or its intracellular domain was reported to drive tissue overgrowth characterized by loss of apical-basal polarity, elevated Yki activity and decreased Ex protein levels (27,28). Although these observations are suggestive of an oncogenic role for Crb, our current study using loss-offunction analysis clearly uncovers a tumor suppressor function for Crb.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…Overexpression of full-length Crb or its intracellular domain was reported to drive tissue overgrowth characterized by loss of apical-basal polarity, elevated Yki activity and decreased Ex protein levels (27,28). Although these observations are suggestive of an oncogenic role for Crb, our current study using loss-offunction analysis clearly uncovers a tumor suppressor function for Crb.…”
Section: Discussionmentioning
confidence: 41%
“…This discrepancy may be due to distinct mutant-neighbor interactions encountered in the different studies. In the overexpression studies, Crb was expressed in whole compartments (27,28), whereas our study examined isolated clones-the latter situation, but not the former, allows interactions between cells with differential Crb activity. It is also possible that Crb overexpression causes a dominant-negative or neomorphic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Since Moe is a negative regulator of Rho1 (Speck et al 2003), upregulation of Rib would be predicted to increase Rho1 activity to mediate its affects on cell morphology. Since Rib also upregulates crb transcription (Kerman et al 2008), and we and others have shown that high Crb levels deregulates the SWH signaling pathway to promote tissue growth Robinson et al 2010), it is possible that suppression of Rho1 activity in rib 1 Ras ACT eye discs unleashes this cryptic activity of Rib in tissue growth via its effect on Crb.…”
Section: Discussionmentioning
confidence: 99%
“…A number of cell polarity and cell adhesion proteins were also found to regulate the Hippo pathway. These include the Scribble (Scrib)-Discs large (Dlg)-Lethal giant larvae (Lgl) complex, atypical protein kinase C (aPKC), Crumbs (Crb) , and Echinoid (Ed) (Chen et al, 2010a;Grzeschik et al, 2010;Ling et al, 2010;Robinson et al, 2010;Yue et al, 2012), indicating a role of cell polarity and cell adhesion in Hippo pathway regulation. Furthermore, two studies identified Tao-1, a STE20 family protein kinase as a positive regulator of the Hippo pathway, possibly by directly phosphorylating and activating the Hpo kinase (Boggiano et al, 2011;Poon et al, 2011).…”
Section: The Drosophila Hippo Pathwaymentioning
confidence: 99%